Cement chromium removal additive and cement-based material and preparation method thereof
By using cement chromium removal additives with calcium sulfide @Fe(II)/Sn(II)@SiO2 structure, the problems of low removal efficiency and secondary pollution in traditional technology are solved, and the cement-based materials are realized Accurate removal of Cr(VI) and improved mechanical properties.
Patent Information
- Application Number
- CN202510014015.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The prior art has low efficiency and possible secondary pollution problems when removing Cr(VI) in cement-based materials, especially traditional reducing additives use corrosion-prone equipment under acidic conditions, and have limited reduction capacity or poor stability.
The cement chromium removal additive with calcium sulfide @Fe(II)/Sn(II)@SiO2 structure is used. This additive coats Fe(II) and Sn(II) sources through a nano-SiO2 layer to form a first-level shell layer and React with calcium hydroxide in an alkaline environment to form a stable co-precipitate to remove Cr(VI).
It effectively avoids the problem of reducing the removal effect caused by the oxidation of additives before contact, and improves the mechanical properties of cement-based materials, while achieving accurate removal of Cr(VI) and avoiding secondary pollution.
Smart Images

Figure CN119390375A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based material preparation, and in particular to a cement chromium removal additive and a cement-based material and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to increase the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information has become the prior art known to ordinary technicians in the field.
[0003] Cr(VI) may be mixed into cement clinker during the production process, including Cr(VI) introduced from iron correction raw materials, industrial waste slag raw materials, chromium slag mineralizers, etc. during cement production, Cr(VI) introduced from chromium-containing grinding bodies during raw material crushing, raw meal and cement grinding, and Cr(VI) introduced from chromium-containing refractory bricks in cement rotary kilns. These Cr(VI) can cause serious harm to buildings, the environment, and human bodies. For example: (1) Due to the strong oxidizing property of Cr(VI), it can corrode the steel bars in cement-based concrete structures, affecting the stability and safety of the building structure. (2) The presence of Cr(VI) can also reduce the bonding force and compressive strength of cement, thereby affecting the quality of the building. (3) Since Cr(VI) is easily soluble in water, it can be transferred from cement buildings to groundwater or surface water through leaching, causing water pollution.
[0004] Chemical method is a common method for removing Cr(VI) from cement-based materials, but traditional reducing additives have various problems. Not only is the efficiency of removing Cr(VI) poor, but it may also cause secondary pollution. For example, sodium sulfite (Na2SO3) as a reducing agent needs to be used under acidic conditions, which is easy to corrode equipment. In addition, the reducing ability of sodium sulfite is limited, and a higher dosage is required to effectively reduce Cr(VI), which increases the treatment cost. Although sodium pyrosulfite (Na2S2O5) is more economical and reasonable as a reducing agent than sodium sulfite, it has poor stability and is easy to decompose, requiring additional stabilization measures. Barium sulfide (BaS) can also be used to precipitate chromium ions, but the resulting precipitate needs further treatment, otherwise it will cause secondary pollution. At the same time, the dosage of barium sulfide needs to be precisely controlled. Excessive dosage will cause residual barium ions and pollute the environment. Summary of the invention
[0005] In view of the above problems, the present invention provides a cement chromium removal additive and a cement-based material and a preparation method thereof, wherein the additive can effectively avoid the problem of reduced removal effect caused by oxidation before contacting Cr(VI) in the cement-based material, and can also improve the mechanical properties of the cement-based material. Specifically, the present invention discloses the technical solution as shown below.
[0006] First, the present invention provides a cement chromium removal additive, which includes a calcium polysulfide inner core, a primary shell layer of Fe(II) and / or Sn(II) source coated on the surface of the inner core, and a secondary shell layer of nano-SiO2 coated on the surface of the primary shell layer, thereby forming the cement chromium removal additive with a calcium polysulfide@Fe(II) / Sn(II)@SiO2 structure.
[0007] Furthermore, the Fe(II) source includes at least one of FeSO4, Fe(NO3)2, FeCl2, etc.
[0008] Furthermore, the Sn(II) source includes at least one of SnSO4, SnCl2, etc.
[0009] Secondly, the present invention provides a cement-based material containing a chromium removal additive, wherein the amount of the chromium removal additive is 0.1-0.3% of the mass of the cement-based material. Preferably, the cement-based material is a silicate cement-based material, so that the calcium hydroxide, a hydration product thereof, reacts with the chromium removal additive to avoid oxidation of the calcium polysulfide before contacting Cr(VI) in the cement-based material.
[0010] Again, the present invention provides a preparation process of the cement chromium removal additive, comprising the following steps: (1) Dissolve the Fe(II) source and / or Sn(II) source in supercritical water, then add calcium polysulfide particles and disperse them evenly to obtain a supercritical suspension mixture for later use.
[0011] (2) The suspension mixture is passed through a microporous plate in a throttle to allow the suspension mixture to rapidly expand into a protective atmosphere collection container, and then the solid product is collected to obtain primary core-shell particles.
[0012] (3) forming a nano-SiO2 seed layer on the surface of the primary core-shell particles by magnetron sputtering technology, and then placing the particles in an alcohol solution containing ammonia water and tetraethyl orthosilicate, heating the reaction under sealed conditions, and then performing ultrasonic treatment, and then collecting the solid product in the reaction solution, and drying it to obtain the chromium removal additive (calcium polysulfide@Fe(II) / Sn(II)@SiO2).
[0013] Furthermore, in step (1), the mass ratio of the Fe(II) source to the Sn(II) source is 0.41-1.27:1.
[0014] Furthermore, in step (1), the ratio of the calcium polysulfide particles to supercritical water is 1-3 g: 30-100 ml. Optionally, the particle size of the calcium polysulfide particles is 10-25 μm.
[0015] Furthermore, in step (1), the method for preparing supercritical water comprises: preheating water to 35-100°C, then pressurizing the water to a pressure of 22.1 MPa, and further heating the water to 374°C under the pressure to obtain water in a supercritical state.
[0016] Furthermore, in step (2), the pore size of the microporous plate in the restrictor is 25-75 μm. Optionally, the protective atmosphere includes any one of nitrogen, argon, etc.
[0017] Furthermore, in step (3), the method for forming the SiO2 seed layer comprises: dropping a mixture of the primary core-shell particles and a non-aqueous organic dispersant on a cleaned silicon wafer, and then spin coating the primary core-shell particles to uniformly distribute the primary core-shell particles on the surface of the silicon wafer. The silicon wafer is then subjected to a heat treatment. After completion, SiO2 is deposited on the surface of the primary core-shell particles on the silicon wafer using a magnetron sputtering technique, thereby forming a SiO2 seed layer.
[0018] Furthermore, the ratio of the primary core-shell particles to the non-aqueous organic dispersant is 1 g: 20-50 ml. Optionally, the non-aqueous organic dispersant includes at least one of anhydrous ethanol, ether, and the like.
[0019] Furthermore, in step (3), the ratio of ammonia water, tetraethyl orthosilicate, and alcohol solution is 3-10 ml: 1-3 ml: 33-100 ml, and the concentration of ammonia water is 1-5 mol / L. Optionally, the alcohol solution includes at least one of anhydrous methanol, anhydrous ethanol, n-propanol, n-butanol, etc.
[0020] Furthermore, in step (3), the heating reaction temperature is 40-80°C and the reaction time is 1-3h, so that the SiO2 seed layer grows into a dense and evenly distributed coating layer.
[0021] Furthermore, in step (3), the ultrasonic treatment time is 1-3 hours, and the ultrasonic power is 300-500W.
[0022] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: 1. Calcium polysulfide will be oxidized to Ca under aerobic conditions. 2+ 、SO4 2- and S 0This is because calcium polysulfide has excellent reducing properties. Therefore, this characteristic of calcium polysulfate can be used to remove Cr(VI) and reduce the highly hazardous Cr(VI) to low-hazard Cr(III). In this process, not only will no substances that cause secondary pollution to cement-based materials be produced, but also the pH value of the system will not be changed, which fully compensates for the many shortcomings of traditional reducing additives. However, the present invention further discovered that when calcium polysulfide is used to remove Cr(VI) from cement-based materials, the calcium polysulfide will be oxidized before contacting Cr(VI), resulting in a low removal efficiency, causing the calcium polysulfide to lose its reducing properties, thereby affecting the removal effect of Cr(VI). To this end, the present invention proposes a calcium polysulfide @Fe(II) / Sn(II)@SiO2 with a special structure and composition, which effectively overcomes the above-mentioned problems and realizes the precise removal of Cr(VI). The reason is: First, the nano-SiO2 layer is coated on the surface of the primary shell layer, which not only protects the calcium polysulfide, but also helps to prevent the Fe(II) and / or Sn(II) in the primary shell layer from being oxidized or converted into hydroxides under the alkaline environment provided by cement hydration, thereby reducing the chromium removal effect. Thus, when the above-mentioned chromium removal agent enters the cement, the nano-SiO2 layer first reacts with the calcium hydroxide provided by cement hydration to form a gelling component CSH. On the one hand, the content of the gelling component in the cement can be increased, which helps to improve the mechanical strength of the cement. On the other hand, after the nano-SiO2 layer reacts, the primary shell layer is exposed, and at this time, the Fe(II) and / or Sn(II) therein undergo an oxidation-reduction reaction with Cr(VI), and the Fe(II) will be oxidized to Fe(III), which is further converted into Fe(OH)3 under the alkaline environment provided by the cement, which can not only act as a catalyst to improve the electron transfer efficiency of removing Cr(VI), but also improve the removal rate of Cr(VI). Moreover, the good adsorption performance of the Fe(OH)3 can adsorb Cr(VI) to form a stable coprecipitate to prevent its diffusion. At the same time, the Sn(II) is oxidized to Sn(IV), which forms [Sn(OH)6] under the alkaline conditions of cement hydration. 2- ions, which serve as ligands to form stable insoluble complexes with Cr(VI), effectively reducing the mobility of Cr(VI). 2-Sn(IV) ions in ionic form are relatively stable in an alkaline environment and are not easily reduced to Sn(II) ions. Secondly, after the above reaction with Fe(II) and Sn(II), Cr(VI) is also converted into Cr(III), thereby converting Cr(VI) into Cr(III) which is more stable, less soluble and less mobile, to prevent the leakage of chromium in cement-based materials. Finally, as the above reaction proceeds, the calcium polysulfide is gradually released, which can react with the Cr(VI) remaining in the cement paste and the above Fe(OH)3, [Sn(OH)6] 2- The Cr(VI) captured by the ions further undergoes an oxidation-reduction reaction, converting Cr(VI) into Cr(III), thereby removing Cr(VI) more thoroughly and making the removal of Cr(VI) more accurate and targeted, thereby improving the removal efficiency. 2+ With SO4 2- Combining with CaSO4 helps to increase the viscosity and hydration rate of cement, thereby improving the early strength and durability of cement.
[0023] 2. When preparing the calcium polysulfide @Fe(II) / Sn(II)@SiO2, the present invention first adopts a method of dissolving the coating material Fe(II) and Sn(II) source in a supercritical fluid, and then rapidly reduces the solubility of the supercritical fluid for the solute by throttling and reducing pressure, so that the Fe(II) and Sn(II) sources precipitate to form solid particles due to supersaturation, and the solid particles are deposited on the surface of the calcium polysulfide to form a uniform thin film to form a primary shell surface as the airflow formed by the supercritical fluid moves, thereby achieving the purpose of uniform, comprehensive and dense coating and modification of the surface of the calcium polysulfide, and forming good protection for the calcium polysulfide. Secondly, the present invention adopts magnetron sputtering technology as an improvement means. Before forming a nano-SiO2 layer on the surface of the primary shell layer, a uniform nano-SiO2 seed layer is first formed on the surface of the primary shell layer, which can induce the uniform development of the formation of nano-SiO2 grains in the subsequent process, so that the nano-SiO2 layer formed on the surface of the primary shell layer is uniform and dense, effectively overcoming the shortcomings of uneven, poor stability and poor dispersibility of the formed nano-SiO2 layer, improving the protection effect of the primary shell layer and the calcium polysulfide core, and avoiding the problem of reduced effectiveness or even failure before contacting Cr(VI). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0025] Figure 1 Schematic diagram of the structure of the throttle used in the following embodiments.
[0026] Figure 2 This is a sample photo of the chromium removal additive prepared in Example 1 below.
[0027] Figure 3 This is a SEM of the chromium removal additive prepared in Example 1 below.
[0028] Figure 4 The following is the XRD test result of the chromium removal additive prepared in Example 1.
[0029] Figure 5 This is a SEM of the chromium removal additive prepared in Example 2 below.
[0030] Figure 6 The following is the XRD test result of the chromium removal additive prepared in Example 2.
[0031] Figure 7 This is a SEM of the chromium removal additive prepared in Example 3 below.
[0032] Figure 8 The following is the XRD test result of the chromium removal additive prepared in Example 3.
[0033] Fig. 9 This is a SEM of the chromium removal additive prepared in Example 4 below.
[0034] Fig.10 The XRD test results of the chromium removal additive prepared in Example 4 below.
[0035] Fig.11 The XRD test results of the chromium removal additive prepared in Example 5 below.
[0036] Fig.12 This is a SEM of the chromium removal additive prepared in Example 6 below.
[0037] Fig.13 The XRD test results of the chromium removal additive prepared in Example 6 below.
[0038] Fig.14 This is a SEM of the chromium removal additive prepared in Example 7 below.
[0039] Fig.15 The XRD test results of the chromium removal additive prepared in Example 7 below.
[0040] Fig.16 This is a SEM of the chromium removal additive prepared in Example 8 below.
[0041] Fig.17 The following are the XRD test results of the chromium removal additive prepared in Example 8.
[0042] Fig.18 This is a SEM of the chromium removal additive prepared in Example 9 below.
[0043] Fig.19 The XRD test results of the chromium removal additive prepared in Example 9 below. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.
[0045] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the specification.
[0046] Example 1 A preparation process of a cement chromium removal additive comprises the following steps: (1) Preheat water to 80°C in a reactor, then pressurize it to 22.1 MPa, and then continue to heat the water to a supercritical state of 374°C to obtain supercritical water. Then, dissolve FeSO4 and SnSO4 in the supercritical water at a mass ratio of 0.41:1, and then add calcium polysulfide particles with a particle size distribution between 10 and 25 μm at a solid-liquid ratio of 1g:30ml and mix evenly to obtain a supercritical suspension mixture for standby use.
[0047] (2) passing the suspension mixture through a microporous plate (such as Figure 1 As shown, the inlet diameter is 11 mm, the outlet diameter is 7 mm, the pore size of the microporous plate is 25 μm, and the arrow indicates the flow direction of the suspension mixture, the same below), the suspension mixture is rapidly expanded and then cooled and depressurized into a collection container under a nitrogen protective atmosphere, and then the solid product is collected to obtain primary core-shell particles for standby use.
[0048] (3) Drop the mixture of the primary core-shell particles and anhydrous ethanol (the ratio of the two is 1g:40ml) on the cleaned silicon wafer, and then use a spin coater to spin coat at a speed of 3000r / min for 30s to evenly distribute the primary core-shell particles on the surface of the silicon wafer. Then place the silicon wafer in a vacuum oven at 60°C and heat for 5min to firmly adhere the primary core-shell particles to the silicon wafer.
[0049] (4) The silicon wafer obtained in step (3) is used as a substrate, and nano-SiO2 is used as a target material. Then, the substrate and the target material are placed in a vacuum chamber of a high vacuum magnetron sputtering apparatus, and an inert gas argon is introduced into the vacuum chamber after high vacuum is evacuated. The power is set to 300 W, and the time is set to 120 seconds before starting sputtering. The SiO2 ejected from the target material is deposited on the substrate, so that the SiO2 is deposited on the surface of the primary core-shell particles to form a SiO2 seed layer.
[0050] (5) The substrate obtained in step (4) is placed in a container containing a mixture of ammonia water (concentration of 1 mol / L), tetraethyl orthosilicate and anhydrous methanol in a volume ratio of 3 ml: 1 ml: 33 ml. The container is sealed and microwave heated to 60°C and kept warm for 2 hours, followed by ultrasonic treatment for 1 hour at an ultrasonic power of 400 W, so that the product attached to the silicon wafer is fully reacted and separated from the solution. Finally, the obtained reaction solution is centrifuged at a rate of 10,000 rpm for 10 minutes, the solid product at the bottom is collected, and it is dried at 60°C under vacuum conditions to a constant weight to obtain a chromium removal additive, such as Figure 2 As shown, the SEM of the chromium removal additive is as follows Figure 3 The XRD test results are shown in Figure 4 shown.
[0051] Performance test: (1) A commercially available 42.5 ordinary Portland cement (the initial concentration of Cr(VI) was measured to be 18.2 mg / kg), standard sand, and mixing water were mixed in a mass ratio of 2:6:1, and the chromium removal additive prepared in this embodiment was added in a ratio of 0.2% of the mass of the cement, and then stirred for 20 minutes to obtain a cement paste. Then, the concentration of Cr(VI) in the cement paste was determined by diphenylcarbazide spectrophotometry, and the removal rate was calculated. The results are shown in Table 1 below. It can be seen that the chromium removal additive has an excellent removal effect on Cr(VI) in cement, which fully complies with the limit of water-soluble chromium (VI) in cement specified in the national standard GB 31893-2015 "Limits and determination methods of water-soluble chromium (VI) in cement" (not higher than 10 mg / kg). (2) The early strength of the specimens prepared from the cement paste was tested according to GBT 17671-2021 "Test method for strength of cement mortar (ISO method)", and the results are shown in Table 1: Table 1 .
[0052] Example 2 A preparation process of a cement chromium removal additive comprises the following steps: (1) Preheat water to 35°C in a reactor, then pressurize it to 22.1MPa, and then continue to heat the water to a supercritical state of 374°C to obtain supercritical water. Then dissolve Fe(NO3)2 and SnSO4 in the supercritical water at a mass ratio of 0.84:1, and then add calcium polysulfide particles with a particle size distribution between 10 and 25μm at a solid-liquid ratio of 2g:70ml and mix evenly to obtain a supercritical suspension mixture for standby use.
[0053] (2) passing the suspension mixture through a microporous plate (such as Figure 1 As shown, the inlet diameter is 11 mm, the outlet diameter is 7 mm, and the pore size of the microporous plate is 50 μm), the suspension mixture is rapidly expanded and then cooled and depressurized into a collection container under a nitrogen protective atmosphere, and then the solid product is collected to obtain primary core-shell particles for later use.
[0054] (3) Drop the mixture of the primary core-shell particles and anhydrous ethanol (the ratio of the two is 1g:30ml) on the cleaned silicon wafer, and then use a spin coater to spin coat at a speed of 3000r / min for 30s to evenly distribute the primary core-shell particles on the surface of the silicon wafer. Then place the silicon wafer in a vacuum oven at 60°C and heat for 5min to firmly adhere the primary core-shell particles to the silicon wafer.
[0055] (4) The silicon wafer obtained in step (3) is used as a substrate, and nano-SiO2 is used as a target material. Then, the substrate and the target material are placed in a vacuum chamber of a high vacuum magnetron sputtering apparatus, and an inert gas argon is introduced into the vacuum chamber after high vacuum is evacuated. The power is set to 300 W, and the time is set to 120 seconds before starting sputtering. The SiO2 ejected from the target material is deposited on the substrate, so that the SiO2 is deposited on the surface of the primary core-shell particles to form a SiO2 seed layer.
[0056] (5) The substrate obtained in step (4) is placed in a container containing a mixture of ammonia water (concentration of 2.5 mol / L), tetraethyl orthosilicate and n-propanol in a volume ratio of 6 ml: 2 ml: 75 ml. The container is sealed and microwave heated to 80°C and kept warm for 1 hour, followed by ultrasonic treatment for 2 hours at an ultrasonic power of 500 W, so that the product attached to the silicon wafer is fully reacted and separated from the solution. Finally, the obtained reaction solution is centrifuged at a rate of 10,000 rpm for 10 minutes, the solid product at the bottom is collected, and it is dried at 60°C under vacuum conditions to a constant weight to obtain a chromium removal additive, and its SEM is as follows: Figure 5 The XRD test results are shown in Figure 6 shown.
[0057] Performance test: (1) A commercially available 42.5 ordinary Portland cement (the initial concentration of Cr(VI) was measured to be 18.2 mg / kg), standard sand, and mixing water were mixed in a mass ratio of 2:6:1, and the chromium removal additive prepared in this embodiment was added at a ratio of 0.15% of the mass of the cement, and then stirred for 20 minutes to obtain a cement paste. Then, the concentration of Cr(VI) in the cement paste was determined by diphenylcarbazide spectrophotometry, and the removal rate was calculated. The results are shown in Table 2 below. It can be seen that the chromium removal additive has an excellent removal effect on Cr(VI) in cement, which fully complies with the limit of water-soluble chromium (VI) in cement specified in the national standard GB 31893-2015 "Limits and determination methods of water-soluble chromium (VI) in cement". (2) The early strength of the test specimens prepared from the cement paste was tested according to GBT17671-2021 "Test method for strength of cement mortar (ISO method)", and the results are shown in Table 2: Table 2 .
[0058] Example 3 A preparation process of a cement chromium removal additive comprises the following steps: (1) Preheat water to 100°C in a reactor, then pressurize it to 22.1 MPa, and then continue to heat the water to a supercritical state of 374°C to obtain supercritical water. Then, dissolve FeCl2 and SnCl2 in the supercritical water at a mass ratio of 1.27:1, and then add calcium polysulfide particles with a particle size distribution of 10-25 μm at a solid-liquid ratio of 3g:100ml and mix evenly to obtain a supercritical suspension mixture for standby use.
[0059] (2) passing the suspension mixture through a microporous plate (such as Figure 1 As shown, the inlet diameter is 11 mm, the outlet diameter is 7 mm, and the pore size of the microporous plate is 75 μm), the suspension mixture is rapidly expanded and then cooled and depressurized into a collection container with an argon protective atmosphere, and then the solid product is collected to obtain primary core-shell particles for later use.
[0060] (3) Drop the mixture of the primary core-shell particles and ether (the ratio of the two is 1g:50ml) on the cleaned silicon wafer, and then use a spin coater to spin coat at a speed of 3000r / min for 30s to evenly distribute the primary core-shell particles on the surface of the silicon wafer. Then place the silicon wafer in a vacuum oven at 60°C and heat for 5min to firmly adhere the primary core-shell particles to the silicon wafer.
[0061] (4) The silicon wafer obtained in step (3) is used as a substrate, and nano-SiO2 is used as a target material. Then, the substrate and the target material are placed in a vacuum chamber of a high vacuum magnetron sputtering apparatus, and an inert gas argon is introduced into the vacuum chamber after high vacuum is evacuated. The power is set to 400 W, and the time is set to 110 seconds before sputtering. The SiO2 ejected from the target material is deposited on the substrate, so that the SiO2 is deposited on the surface of the primary core-shell particles to form a SiO2 seed layer.
[0062] (5) The substrate obtained in step (4) is placed in a container containing a mixture of ammonia water (concentration of 5 mol / L), tetraethyl orthosilicate and anhydrous ethanol in a volume ratio of 10 ml: 3 ml: 100 ml. The container is sealed and microwave heated to 50°C and kept warm for 2 hours, followed by ultrasonic treatment for 2 hours at an ultrasonic power of 300 W, so that the product attached to the silicon wafer is fully reacted and separated from the solution. Finally, the obtained reaction solution is centrifuged at a rate of 10,000 rpm for 10 minutes, the solid product at the bottom is collected, and it is dried at 60°C under vacuum conditions to a constant weight to obtain a chromium removal additive, and its SEM is as follows: Figure 7 The XRD test results are shown in Figure 8 shown.
[0063] Performance test: (1) A commercially available 42.5 ordinary Portland cement (the initial concentration of Cr(VI) was measured to be 18.2 mg / kg), standard sand, and mixing water were mixed in a mass ratio of 2:6:1, and the chromium removal additive prepared in this embodiment was added at a ratio of 0.3% of the mass of the cement, and then stirred for 20 minutes to obtain a cement paste. Then, the concentration of Cr(VI) in the cement paste was determined by diphenylcarbazide spectrophotometry, and the removal rate was calculated. The results are shown in Table 3 below. It can be seen that the chromium removal additive has an excellent removal effect on Cr(VI) in cement, which fully complies with the limit of water-soluble chromium (VI) in cement specified in the national standard GB 31893-2015 "Limits and determination methods of water-soluble chromium (VI) in cement". (2) The early strength of the test specimens prepared from the cement paste was tested according to GBT17671-2021 "Test method for strength of cement mortar (ISO method)", and the results are shown in Table 3: Table 3 .
[0064] Example 4 A preparation process of a cement chromium removal additive comprises the following steps: (1) Preheat water to 50°C in a reactor, then pressurize it to 22.1 MPa, and then continue to heat the water to a supercritical state of 374°C to obtain supercritical water. Then, SnSO4 is dissolved in the supercritical water to form a saturated solution, and then calcium polysulfide particles with a particle size distribution between 10 and 25 μm are added in a solid-liquid ratio of 2.5 g: 60 ml and mixed evenly to obtain a supercritical suspension mixture for standby use.
[0065] (2) passing the suspension mixture through a microporous plate (such as Figure 1 As shown, the inlet diameter is 11 mm, the outlet diameter is 7 mm, and the pore size of the microporous plate is 40 μm), so that the suspension mixed liquid is rapidly expanded and then cooled and depressurized to a collection container in a nitrogen protective atmosphere, and then the solid product is collected to obtain primary core-shell particles for standby use.
[0066] (3) Drop the mixture of the primary core-shell particles and ether (the ratio of the two is 1g:20ml) on the cleaned silicon wafer, and then use a spin coater to spin coat at a speed of 3000r / min for 30s to evenly distribute the primary core-shell particles on the surface of the silicon wafer. Then place the silicon wafer in a vacuum oven at 60°C and heat for 5min to firmly adhere the primary core-shell particles to the silicon wafer.
[0067] (4) The silicon wafer obtained in step (3) is used as a substrate, and nano-SiO2 is used as a target material. Then, the substrate and the target material are placed in a vacuum chamber of a high vacuum magnetron sputtering apparatus, and an inert gas argon is introduced into the vacuum chamber after high vacuum is evacuated. The power is set to 300 W, and the time is set to 120 seconds before starting sputtering. The SiO2 ejected from the target material is deposited on the substrate, so that the SiO2 is deposited on the surface of the primary core-shell particles to form a SiO2 seed layer.
[0068] (5) The substrate obtained in step (4) is placed in a container containing a mixture of ammonia water (concentration of 4 mol / L), tetraethyl orthosilicate and n-butanol in a volume ratio of 8 ml:2.5 ml:90 ml. The container is sealed and microwave heated to 40°C and kept warm for 3 hours, followed by ultrasonic treatment for 3 hours at an ultrasonic power of 450 W, so that the product attached to the silicon wafer is fully reacted and separated from the solution. Finally, the obtained reaction solution is centrifuged at a rate of 10,000 rpm for 10 minutes, and the solid product at the bottom is collected and dried at 60°C under vacuum conditions to a constant weight to obtain a chromium removal additive, whose SEM is as follows: Fig. 9 The XRD test results are shown in Fig.10 shown.
[0069] Performance test: (1) A commercially available 42.5 ordinary Portland cement (the initial concentration of Cr(VI) was measured to be 18.2 mg / kg), standard sand, and mixing water were mixed in a mass ratio of 2:6:1, and the chromium removal additive prepared in this embodiment was added at a ratio of 0.1% of the mass of the cement, and then stirred for 20 minutes to obtain a cement paste. Then, the concentration of Cr(VI) in the cement paste was determined by diphenylcarbazide spectrophotometry, and the removal rate was calculated. The results are shown in Table 4 below. It can be seen that the chromium removal additive has an excellent removal effect on Cr(VI) in cement, which fully complies with the limit of water-soluble chromium (VI) in cement specified in the national standard GB 31893-2015 "Limits and determination methods of water-soluble chromium (VI) in cement". (2) The early strength of the test specimens prepared from the cement paste was tested according to GBT17671-2021 "Test method for strength of cement mortar (ISO method)", and the results are shown in Table 4: Table 4 .
[0070] Example 5 (1) A commercially available 42.5 ordinary Portland cement (the initial concentration of Cr(VI) was measured to be 18.2 mg / kg), standard sand, and mixing water were mixed in a mass ratio of 2:6:1, and a chromium removal additive (calcium polysulfide powder with a particle size distribution between 10 and 25 μm) was added in a ratio of 0.2% of the mass of the cement. The XRD test results are as follows: Fig.11 As shown), and then stirred for 20 minutes to obtain cement paste. Then the concentration of Cr(VI) in the cement paste was determined by diphenylcarbazide spectrophotometry, and the removal rate was calculated. The results are shown in Table 5 below. It can be seen that the chromium removal additive has insufficient removal effect on Cr(VI) in cement, resulting in the chromium (VI) content in the cement paste not meeting the limit in the national standard GB 31893-2015 "Limits and determination methods of water-soluble chromium (VI) in cement". (2) The early strength of the test specimens prepared from the cement paste was tested according to GBT 17671-2021 "Test method for strength of cement mortar (ISO method)", and the results are shown in Table 5: Table 5 .
[0071] Example 6 A preparation process of a cement chromium removal additive, which is the same as the above-mentioned embodiment 1, except that the supercritical suspension mixed solution of this embodiment is prepared by the following method: water is placed in a reaction kettle and preheated to 80°C, then pressurized to 22.1MPa, and then the water is further heated to a supercritical state of 374°C to obtain supercritical water. Then, calcium polysulfide particles with a particle size distribution between 10 and 25 μm are added in a solid-liquid ratio of 1g:30ml and mixed evenly to obtain a supercritical suspension mixed solution.
[0072] The SEM image of the cement chromium removal additive prepared in this example is as follows: Fig.12 The XRD test results are shown in Fig.13 shown.
[0073] Performance test: (1) A commercially available 42.5 ordinary Portland cement (the initial concentration of Cr(VI) was measured to be 18.2 mg / kg), standard sand, and mixing water were mixed in a mass ratio of 2:6:1, and the chromium removal additive prepared in this embodiment was added at a ratio of 0.2% of the mass of the cement, and then stirred for 20 minutes to obtain a cement paste. Then, the concentration of Cr(VI) in the cement paste was determined by diphenylcarbazide spectrophotometry, and the removal rate was calculated. The results are shown in Table 6 below. It can be seen that the content of chromium (VI) in the cement paste meets the limit in the national standard GB 31893-2015 "Limits and determination methods of water-soluble chromium (VI) in cement", but the removal effect of the chromium removal additive on Cr(VI) in cement is significantly reduced. (2) The early strength of the test specimens prepared from the cement paste was tested according to GBT17671-2021 "Test method for strength of cement mortar (ISO method)", and the results are shown in Table 6: Table 6 .
[0074] Example 7 A preparation process of a cement chromium removal additive comprises the following steps: (1) Preheat water to 35°C in a reactor, then pressurize it to 22.1MPa, and then continue to heat the water to a supercritical state of 374°C to obtain supercritical water. Then dissolve Fe(NO3)2 and SnSO4 in the supercritical water at a mass ratio of 0.84:1, and then add calcium polysulfide particles with a particle size distribution between 10 and 25μm at a solid-liquid ratio of 2g:70ml and mix evenly to obtain a supercritical suspension mixture for standby use.
[0075] (2) passing the suspension mixture through a microporous plate (such as Figure 1As shown in the figure, the inlet diameter is 11 mm, the outlet diameter is 7 mm, and the pore size of the microporous plate is 50 μm), the suspension mixed liquid is rapidly expanded and then cooled and depressurized to a collection container in a nitrogen protective atmosphere, and then the solid product is collected. The obtained primary core-shell particles are used as a chromium removal additive, and its SEM is as follows Fig.14 The XRD test results are shown in Fig.15 shown.
[0076] Performance test: (1) A commercially available 42.5 ordinary Portland cement (the initial concentration of Cr(VI) was measured to be 18.2 mg / kg), standard sand, and mixing water were mixed in a mass ratio of 2:6:1, and the chromium removal additive prepared in this embodiment was added at a ratio of 0.15% of the mass of the cement, and then stirred for 20 minutes to obtain a cement slurry. Then, the concentration of Cr(VI) in the cement slurry was determined by diphenylcarbazide spectrophotometry, and the removal rate was calculated. The results are shown in Table 7 below. It can be seen that the chromium removal additive prepared in this embodiment has a significantly reduced ability to remove Cr(VI) from cement. (2) According to GBT 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", the early strength of the test specimens prepared from the cement slurry was tested, and the results are shown in Table 7: Table 7 .
[0077] Example 8 A preparation process of a cement chromium removal additive comprises the following steps: (1) Preheat water to 100°C in a reactor, then pressurize it to 22.1 MPa, and then continue to heat the water to a supercritical state of 374°C to obtain supercritical water. Then, dissolve FeCl2 and SnCl2 in the supercritical water at a mass ratio of 1.27:1, and then add calcium polysulfide particles with a particle size distribution of 10-25 μm at a solid-liquid ratio of 3g:100ml and mix evenly to obtain a supercritical suspension mixture for standby use.
[0078] (2) passing the suspension mixture through a microporous plate (such as Figure 1 As shown, the inlet diameter is 11 mm, the outlet diameter is 7 mm, and the pore size of the microporous plate is 75 μm), the suspension mixture is rapidly expanded and then cooled and depressurized into a collection container with an argon protective atmosphere, and then the solid product is collected to obtain primary core-shell particles for later use.
[0079] (3) Drop the mixture of the primary core-shell particles and ether (the ratio of the two is 1g:50ml) on the cleaned silicon wafer, and then use a spin coater to spin coat at a speed of 3000r / min for 30s to evenly distribute the primary core-shell particles on the surface of the silicon wafer. Then place the silicon wafer in a vacuum oven at 60°C and heat for 5min to firmly adhere the primary core-shell particles to the silicon wafer.
[0080] (4) The silicon wafer obtained in step (3) is placed in a container containing a mixture of ammonia water (concentration of 5 mol / L), tetraethyl orthosilicate and anhydrous ethanol in a volume ratio of 10 ml: 3 ml: 100 ml. The container is sealed and microwave heated to 50°C and kept warm for 2 hours, followed by ultrasonic treatment for 2 hours at an ultrasonic power of 300 W, so that the product attached to the silicon wafer is fully reacted and separated from the solution. Finally, the obtained reaction solution is centrifuged at a rate of 10,000 rpm for 10 minutes, the solid product at the bottom is collected, and it is dried at 60°C under vacuum conditions to a constant weight to obtain a chromium removal additive, and its SEM is as follows: Fig.16 The XRD test results are shown in Fig.17 shown.
[0081] Performance test: (1) A commercially available 42.5 ordinary Portland cement (the initial concentration of Cr(VI) was measured to be 18.2 mg / kg), standard sand, and mixing water were mixed in a mass ratio of 2:6:1, and the chromium removal additive prepared in this embodiment was added at a ratio of 0.3% of the mass of the cement, and then stirred for 20 minutes to obtain a cement slurry. Then, the concentration of Cr(VI) in the cement slurry was determined by diphenylcarbazide spectrophotometry, and the removal rate was calculated. The results are shown in Table 8 below. It can be seen that the chromium removal additive prepared in this embodiment has a significantly reduced ability to remove Cr(VI) from cement. (2) According to GBT 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", the early strength of the test specimens prepared from the cement slurry was tested, and the results are shown in Table 8: Table 8 .
[0082] Example 9 A preparation process of a cement chromium removal additive is the same as that of the above-mentioned embodiment 2, except that the primary core-shell particles of this embodiment are prepared by the following method: (1) Dissolve Fe(NO3)2 and SnSO4 in water at a mass ratio of 0.84:1, then add calcium polysulfide particles with a particle size distribution between 10 and 25 μm at a solid-liquid ratio of 2g:70ml and mix evenly to obtain a suspended mixed liquid for later use.
[0083] (2) The suspended mixed liquid is dried in a nitrogen atmosphere to remove moisture, and then the solid product is collected and used as a cement chromium removal additive. The SEM of the solid product is as follows: Fig.18 The XRD test results are shown in Fig.19 shown.
[0084] Performance test: (1) A commercially available 42.5 ordinary Portland cement (the initial concentration of Cr(VI) was measured to be 18.2 mg / kg), standard sand, and mixing water were mixed in a mass ratio of 2:6:1, and the chromium removal additive prepared in this embodiment was added at a ratio of 0.15% of the mass of the cement, and then stirred for 20 minutes to obtain a cement slurry. Then, the concentration of Cr(VI) in the cement slurry was determined by diphenylcarbazide spectrophotometry, and the removal rate was calculated. The results are shown in Table 9 below. It can be seen that the chromium removal additive has insufficient effect on the removal of Cr(VI) in cement, resulting in a significant decrease in the removal rate of chromium(VI) in the cement slurry. (2) According to GBT 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", the early strength of the test specimens prepared from the cement slurry was tested, and the results are shown in Table 9: Table 9 .
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A cement chromium removal additive, characterized in that: The cement chromium removal additive comprises a calcium polysulfide inner core, a primary shell layer of Fe(II) and / or Sn(II) source coated on the surface of the inner core, and a secondary shell layer of nano-SiO2 coated on the surface of the primary shell layer, thereby forming a calcium polysulfide@Fe(II) / Sn(II)@SiO2 structure.
2. The cement chromium removal additive according to claim 1, characterized in that: The Fe(II) source includes at least one of FeSO4, Fe(NO3)2, and FeCl2.
3. The cement chromium removal additive according to claim 1 or 2, characterized in that: The Sn(II) source includes at least one of SnSO4 and SnCl2.
4. A cement-based material containing the cement chromium removal additive according to any one of claims 1 to 3, characterized in that: The dosage of the chromium removal additive is 0.1~0.3% of the mass of the cement-based material.
5. The cement-based material according to claim 4, characterized in that: The cement-based material is a silicate cement-based material.
6. The preparation process of the cement chromium removal additive according to any one of claims 1 to 3, characterized in that: The steps include: (1) dissolving an Fe(II) source and / or a Sn(II) source into supercritical water, and then adding calcium polysulfide particles therein to disperse them uniformly to obtain a supercritical suspension mixture for later use; (2) passing the suspension mixture through a microporous plate in a throttle to allow the suspension mixture to rapidly expand into a protective atmosphere collection container, and then collecting the solid product to obtain primary core-shell particles; (3) forming a nano-SiO2 seed layer on the surface of the primary core-shell particles by magnetron sputtering technology, and then placing the particles in an alcohol solution containing ammonia water and tetraethyl orthosilicate, heating the reaction under sealed conditions, and then performing ultrasonic treatment, and then collecting the solid product in the reaction solution, and drying it to obtain the chromium removal additive.
7. The preparation process of the cement chromium removal additive according to claim 6, characterized in that: In step (1), the ratio of the Fe(II) source to the Sn(II) source is 0.41-1.27:1; Alternatively, in step (1), the ratio of the calcium polysulfide particles to supercritical water is 1-3 g: 30-100 ml; Alternatively, in step (1), the particle size of the calcium polysulfide particles is 10-25 μm.
8. The preparation process of the cement chromium removal additive according to claim 6, characterized in that: In step (2), the pore size of the microporous plate in the restrictor is 25-75 μm; Alternatively, in step (2), the protective atmosphere includes any one of nitrogen and argon.
9. The preparation process of the cement chromium removal additive according to claim 6, characterized in that: In step (3), the method for forming the SiO2 seed layer comprises: dropping a mixed solution of the primary core-shell particles and a non-aqueous organic dispersant on a cleaned silicon wafer, and then spin coating to uniformly distribute the primary core-shell particles on the surface of the silicon wafer; then heating the silicon wafer; and after completion, using magnetron sputtering technology to deposit SiO2 on the surface of the primary core-shell particles on the silicon wafer, thereby forming a SiO2 seed layer; Alternatively, the ratio of the primary core-shell particles to the non-aqueous organic dispersant is 1 g: 20-50 ml; Alternatively, the non-aqueous organic dispersant includes at least one of anhydrous ethanol and ether.
10. The preparation process of the cement chromium removal additive according to any one of claims 6 to 9, characterized in that: In step (3), the ratio of ammonia water, tetraethyl orthosilicate and alcohol solution is 3-10 ml: 1-3 ml: 33-100 ml. Alternatively, in step (3), the concentration of the ammonia water is 1-5 mol / L; Alternatively, in step (3), the alcohol solution includes at least one of anhydrous methanol, anhydrous ethanol, n-propanol, and n-butanol; Alternatively, in step (3), the heating reaction temperature is 40-80°C and the reaction time is 1-3h; Alternatively, in step (3), the ultrasonic treatment time is 1 to 3 hours, and the ultrasonic power is 300 to 500 W.
Citation Information
Patent Citations
Calcium polysulfide vulcanized zero-valent iron nano composite material as well as preparation method and application thereof
CN113996315A
Ferrous sulfate-antimony trisulfide composite liquid chromium removal agent as well as preparation method and application thereof
CN114213056A
Cement hexavalent chromium reducing agent and preparation method thereof
CN114644477A
Three-layer core-shell structure iron-based nano-particle and preparation method and application thereof
CN115634674A
Supercritical impact flow method for wrapping micro granule
CN1879957A